Glutaric acidemia type I: Case report in pediatrics (Research, Society and Development, 2024)
Objective: To analyze the diagnosis, evolution and treatment of type I glutaric acidemia in a pediatric patient. Methodology: This research was carried out through a case study, of a descriptive nature, in which the aforementioned pathology and its interfaces in a pediatric patient were evaluated in order to analyze each phase and its most important complications during the treatment period at HUMAP. Results: The patient underwent imaging, laboratory and genetic tests, in the search for a conclusive etiological diagnosis, in addition, the most striking characteristics of AG-I pathology were neurological symptoms, such as changes in tone, axial hypotonia, changes in strength, irritability and epileptic seizures. Conclusion: Patient still undergoing treatment at this institution, maintaining an improvement in irritability and control of epileptic seizures with the use of oxycarbazepime, use of a specific formula with lysine restriction enriched with vitamins and minerals, with significant improvement in the condition, after approximately 30 days.